Efficacy of Favipiravir in treatment of mild & moderate COVID-19 infection in Nepal: a multi-center, randomized, open-labelled, phase III clinical trial. (March 2022) - Adhikari, P.; Koirala, J.; Shrestha, A.; Bista, N.; Maleku, K.; Das, J.; Bhandari, K.; Adhikari, N.; Rawal, A.; Pandit, K.; Gyawali, P.; Pant, S.
Abstract : Purpose: To study tolerability and outcome of oral favipiravir treatment among COVID-19 patients in Nepal. Methods & Materials: In this multi-centered randomized, open-labelled phase III clinical trial, we enrolled 18-80 years old, RT-PCR confirmed patients with mild to moderate COVID-19 infection from 9 participating hospitals of Nepal, within 6 days of onset of symptoms. The investigational product (Favipiravir) was compared against placebo in patients with mild infection and against Remdesivir in moderate infection. Patients who met the eligibility criteria were randomly enrolled in the study after taking informed consent. This is a preliminary report of the data analysis. Results: At the time of this preliminary data analysis, 90 cases were enrolled in the study including 70 mild and 20 moderate cases (see table). Among the participants with mild COVID19 infection, clinical improvement was noted in 30 (78.9%) and 27 (84.4%) patients who received Favipiravir and placebo, respectively (p=0.78). While among the participants with moderate infection, 9 (81%) and 8 (88.9%) patients who received Favipiravir and Remdesivir, respectively, had clinical improvement (p=1). Patients tolerated Favipiravir well with only 3 (6.12 %) patients showing adverse events, which were mainly elevated liver function test & uric acid level, both considered minor. None of the patients receiving placebo or remdesivir reported any adverse events. Conclusion: The investigational product has been tolerated well by this group of patients with only mild and reversible side effects in 6.12 % cases. The outcomes between the study groups were comparable.